Strategi Jepang Menghadapi Rusia Terhadap Sengketa Kepulauan Kuril Tahun 2008-2012 - Sandra Monica; Idjang Tjarsono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This study will explain about Japanese strategy against Russia on Kuril Islands dispute. Problems that have occurred impact on the bilateral relationship between Japan and Russia. During the conflict between the two countries do confrontation that resulted in this conflict continues to take place. Strategies that do claim the Japanese in the other Kuril Islands between Japan cooperate with the United States in the field of defense, japan use international law to pressure Russia in ownership Kuril Islands, Japan using the Vienna Convention to strengthen its position on the Kuril Islands, Japan withdrew its ambassador from RussiaKeywords: Kuril Islands, Japanese strategy, defense cooperation, the Law Internasioanal.